Reliability, Maintainability and Risk : Practical Methods for Engineers - Smith, David J. (David John), 1943 June 22- (Butterworth-Heinemann, an imprint of Elsevier, 2017)
Reliability, Maintainability and Risk: Practical Methods for Engineers, Ninth Edition, has taught reliability and safety engineers techniques to minimize process design, operation defects, and failures for 35 years. For beginners, the book provides tactics on how to avoid pitfalls in this complex and wide field. For experts in the field, well-described, realistic, and illustrative examples and case studies add new insight and assistance. The author uses his 40 years of experience to create a comprehensive and detailed guide to the field, also providing an excellent description of reliability and risk computation concepts.